The Impact on Thai Workers Caused by the Employment of Migrant Workers and Opinions Regarding the Strategic Management of Migrant Workers in Thailand - Noknoi, Chetsada; Langthaekun, Sunchai (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aims to study the impact on Thai workers caused by the use of migrant workers, as well as the opinions regarding the strategic management of migrant workers in Thailand. The sample used for this study comprised 322 Thai workers employed by entrepreneurs in Songkhla province. A questionnaire was used as the instrument for data collection. The statistics used in this study were percentage, mean, standard deviation, t-test, ANOVA and the Pearson correlation coefficient at the level of significance .05. The results showed that the overall impact on Thai workers of employing migrant workers was at a moderate level. Considering each aspect individually revealed that the effect was at a moderate level for all aspects, including the work, compensation, job security, psychological, and social aspects. In terms of the opinions regarding the strategic management of migrant workers in Thailand, the respondents agreed at a moderate level. The hypothesis test firstly found that Thai workers with different education levels were affected differently by the employment of migrant workers overall, but especially with regards to compensation and job security. Secondly, it was found that Thai workers with different levels of education and work factors (i.e., work type and the number of employees working in an establishment) had different opinions regarding the strategic management of migrant workers in Thailand. Finally, the overall impact of the employment of migrant workers on Thai workers had no relation to opinions regarding the strategic management of migrant workers in Thailand.